2021
DOI: 10.2169/internalmedicine.5078-20
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Relevance of Nightly Sleep Duration to Metabolic, Anthropometric, and Lifestyle Factors in Patients with Type 2 Diabetes

Abstract: Objective Although a number of studies have shown that both short and long sleep durations were associated with the risk of metabolic disorders related to obesity, the underlying mechanism is still not fully understood. In this study, we analyzed the association of sleep duration with metabolic, anthropometric, and lifestyle factors in patients with type 2 diabetes. Patients and Methods The subjects were 279 patients with type 2 diabetes 63 (52-70) years old (median and interquartile range) with a body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
0
0
1
Order By: Relevance
“…The volunteers who reported altered sleep had lower AMS. Sleep disorders are related to a lower level of physical activity, 66,67 thus corroborating the present study, which observed lower AMS in the irregularly active/sedentary elderly. Noteworthy, insufficient physical activity is a known factor for lower MS. 68 In this context, physical inactivity in diabetic elderly may be associated with sleep disorders and physical, emotional, and cognitive changes, especially physical and cognitive disability, as well as depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The volunteers who reported altered sleep had lower AMS. Sleep disorders are related to a lower level of physical activity, 66,67 thus corroborating the present study, which observed lower AMS in the irregularly active/sedentary elderly. Noteworthy, insufficient physical activity is a known factor for lower MS. 68 In this context, physical inactivity in diabetic elderly may be associated with sleep disorders and physical, emotional, and cognitive changes, especially physical and cognitive disability, as well as depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Contudo, em nossa investigação não foi encontrada associação estatisticamente significativa entre a duração do sono e o consumo energético diário total, o que também foi visto por Nakayama et al (2021) e Castro et al (2019). Todavia, um menor valor médio de quilocalorias totais foi observado no grupo de longa duração do sono, corroborando a hipótese de que a longa duração do sono leva a um menor consumo de energia nas refeições principais -desjejum, almoço e jantar (KANT; GRAUBARD, 2014;KIM;DEROO;SANDLER, 2011).…”
Section: Discussionunclassified